2020
DOI: 10.1016/j.csbj.2020.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods for the estimation of contagion effects in human disease and health networks

Abstract: Contagion effects, sometimes referred to as spillover or influence effects, have long been central to the study of human disease and health networks. Accurate estimation and identification of contagion effects are important in terms of understanding the spread of human disease and health behavior, and they also have various implications for designing effective public health interventions. However, many challenges remain in estimating contagion effects and it is often unclear when it is difficult to correctly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Similarities of behavior, state, and characteristics of two individuals in a network relationship can be caused by three primary mechanisms: influence, homophilous selection, or common socialenvironmental factors (Vanderweele and An, 2013). While it is possible to rule out some mechanisms through random treatment assignment or networks in experiments, entanglement among these different mechanisms makes it difficult to correctly estimate social influence effects from observational data (Xu, 2020). The challenges in estimation caused by entanglement among social influence effects and common social-environmental factors can be easily framed as an omitted variable bias problem (e.g., ignoring the group or environment individuals belong to when estimating the social influence model).…”
Section: Identification Of Social Influence As An Omitted Variable Bi...mentioning
confidence: 99%
“…Similarities of behavior, state, and characteristics of two individuals in a network relationship can be caused by three primary mechanisms: influence, homophilous selection, or common socialenvironmental factors (Vanderweele and An, 2013). While it is possible to rule out some mechanisms through random treatment assignment or networks in experiments, entanglement among these different mechanisms makes it difficult to correctly estimate social influence effects from observational data (Xu, 2020). The challenges in estimation caused by entanglement among social influence effects and common social-environmental factors can be easily framed as an omitted variable bias problem (e.g., ignoring the group or environment individuals belong to when estimating the social influence model).…”
Section: Identification Of Social Influence As An Omitted Variable Bi...mentioning
confidence: 99%
“…China is reported to be the only major economy in the world to achieve positive growth in 2020, with a growth rate of 2.3 percent. 1 It is no denying that contagion effects have always been the focus of human disease and health network research [1][2] empirically analyzed three types networks of disease transmission, namely, temporary networks, static networks, and a fully connected topology. Results showed that time structure can affect disease transmission more than static network structure.…”
Section: Introductionmentioning
confidence: 99%